Robotic versus laparoscopic right colectomy with complete mesocolon excision for right-sided colon cancer: a systematic review and meta-analysis - Chaouch, Mohamed Ali; Gouader, Amine; Krimi, Bassem; Daghmouri, Mohamed Aziz; Bianchi, Paolo Pietro; Piozzi, Guglielmo Niccolò; Khan, Jim S.; Fattal, Mohamad Wahid; Reißfelder, Christoph; Oweira, Hani (BMC surgery, 2025)
Right colectomy with complete mesocolic excision (CME) is considered the standard for right-sided colon cancer. While laparoscopic CME (LCME) is widely performed, robotic CME (RCME) has emerged as an alternative approach. This systematic review and meta-analysis compared the perioperative, pathological, and oncological outcomes of RCME and LCME.